Labor resources in the agriculture of Ukraine and their financial security: regional aspect - Totska, Olesia (National Interest, 2022)
Financial and quantitative indicators characterizing work in the agricultural economy of Ukraine have regional differences. The purpose of this study is a comprehensive analysis of the regions of Ukraine in terms of the number and incomes of full-time agricultural workers. The following methods were used to realize the set goal: ranking – to determine the position of each region of Ukraine according to selected financial and quantitative indicators of labor in agriculture; graphic – for the zoning of the regions of Ukraine depending on the received positions based on the results of the rating. It was determined that in 2021, the average registered number of full-time agricultural workers in the regions of Ukraine ranged from 1.2 thousand people (Transcarpathian region) to 29.7 thousand people (Poltava region). Poltava, Kyiv, and Cherkasy regions are the leaders in this indicator; Ivano-Frankivsk, Chernivtsi and Zakarpattia regions are outsiders. At the same time, the average monthly salary of full-time agricultural workers in the regions of Ukraine in the analyzed period ranged from 259.2 euros (Odesa region) to 504.1 euros (Ivano-Frankivsk region). Ivano-Frankivsk, Ternopil, and Lviv regions are the leaders in terms of financial indicators; Rivne, Chernivtsi and Odesa regions are outsiders. According to the levels of the number of full-time agricultural workers and their wages, the regions of Ukraine are classified into seven different zones. Only eight regions or 32% fell into zones with a clear position (very high, high, medium, low and very low level), all other regions fell into zones of imbalances.